Efficacy of Oral Hygiene Aids in Gingivitis Management: A Comparative Study of Manual and Electric Toothbrushes, Dental Floss, and Mouthwash - Civy V. Pulayath; Fathimath Al Zahrath; Ajith A. Chandy; Harish Chandran; Shanthi Menezes; Harshvardhan N. Jain (Journal of Pharmacy and Bioallied Sciences)
Background: Gingivitis is a prevalent oral health issue characterized by inflammation of the gums, often resulting from inadequate plaque removal. Materials and Methods: A randomized controlled trial was conducted with 120 participants diagnosed with gingivitis, aged 18 to 65 years. Participants were divided into four groups: Group A used a manual toothbrush, Group B used an electric toothbrush, Group C used dental floss in addition to manual brushing, and Group D used mouthwash in addition to manual brushing. The study duration was eight weeks, with gingival index (GI) scores recorded at baseline, four weeks, and eight weeks. Plaque index (PI) and bleeding on probing (BOP) were also assessed as secondary outcomes. Results: At the end of eight weeks, Group B (electric toothbrush) showed the most significant reduction in gingival index scores (mean reduction: 1.2, P < 0.01), followed by Group D (mouthwash) with a mean reduction of 1.0 (P < 0.05). Group C (dental floss) exhibited a moderate reduction (mean reduction: 0.8, P < 0.05), while Group A (manual toothbrush) had the least improvement (mean reduction: 0.5, P = 0.08). Plaque index and bleeding on probing results followed a similar trend, with the electric toothbrush group demonstrating superior outcomes. Conclusion: The study concludes that electric toothbrushes are more effective in managing gingivitis compared to manual toothbrushes, dental floss, and mouthwash.